Evidence of Carotid Atherosclerosis Vulnerability Regression in Real Life From Magnetic Resonance Imaging: Results of the MAGNETIC Prospective Study - Oronzo Catalano; Giulia Bendotti; Teresa L. Aloi; Alberto Ferrari Bardile; Mirella Memmi; Patrick Gambelli; Daniela Zanaboni; Alessandra Gualco; Emanuela Cattaneo; Antonio Mazza; Mauro Frascaroli; Esmeralda Eshja; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Atherosclerosis vulnerability regression has been evidenced mostly in randomized clinical trials with intensive lipid‐lowering therapy. We aimed to demonstrate vulnerability regression in real life, with a comprehensive quantitative method, in patients with asymptomatic mild to moderate carotid atherosclerosis on a secondary prevention program. Methods and Results We conducted a single‐center prospective observational study (MAGNETIC [Magnetic Resonance Imaging as a Gold Standard for Noninvasive Evaluation of Atherosclerotic Involvement of Carotid Arteries]): 260 patients enrolled at a cardiac rehabilitation center were followed for 3 years with serial magnetic resonance imaging. Per section cutoffs (95th/5th percentiles) were derived from a sample of 20 consecutive magnetic resonance imaging scans: (1) lipid‐rich necrotic core: 26% of vessel wall area; (2) intraplaque hemorrhage: 12% of vessel wall area; and (3) fibrous cap: (a) minimum thickness: 0.06 mm, (b) mean thickness: 0.4 mm, (c) projection length: 11 mm. Patients with baseline magnetic resonance imaging of adequate quality (n=247) were classified as high (n=63, 26%), intermediate (n=65, 26%), or low risk (n=119, 48%), if vulnerability criteria were fulfilled in ≥2 contiguous sections, in 1 or multiple noncontiguous sections, or in any section, respectively. Among high‐risk patients, a conversion to any lower‐risk status was found in 11 (17%; P=0.614) at 6 months, in 16 (25%; P=0.197) at 1 year, and in 19 (30%; P=0.009) at 3 years. Among patients showing any degree of carotid plaque vulnerability, 21 (16%; P=0.014) were diagnosed at low risk at 3 years. Conclusions This study demonstrates with a quantitative approach that vulnerability regression is common in real life. A secondary prevention program can promote vulnerability regression in asymptomatic patients in the mid to long term.